School management teams’ and parents’ collaborative strategies to enhance learner academic performance - Radebe, Philile (University of the Free State, 2024)
Scholars from across the globe have conducted studies and recognised the importance of parents -schools collaborations. South Africa and other nations have adopted several policies and initiatives requiring parents to be involved in their children's education because research demonstrates that learners benefit when schools and parents work together. The study aimed to explore the collaborative strategies of SMTs and parents to enhance learners' academic performance. The following secondary questions guided the study: How do SMTs and parents collaborate to enhance learner academic performance? What challenges do SMTs and parents experience with their collaborative strategies to enhance learner academic performance? What can be done to enhance effective collaborative strategies between the SMTs and parents? Grounded in collaborative leadership theory, the study adopted an interpretive paradigm and employed a qualitative approach. The study used a multiple case study design. Purposive sampling was used to select participants, including two School Governing Body (SGB) parents, one principal, and one Head of Department (HOD) from each of the five schools in Thabo Mofutsanyana District. Data collection methods included semi-structured interviews and document analysis. Data analysis using thematic analysis revealed four key themes: conceptualisation of collaboration, experiences on parent-school collaboration, challenges on parent-school collaboration, and strategies for enhancing parent-school collaboration. The key findings indicate that although all participant groups recognise the importance of collaboration, obstacles such as limited communication, resource shortages, and a lack of trust impede its effectiveness. The study suggests several strategies to improve collaboration, including holding regular meetings, using various communication platforms, implementing policies, and encouraging active parent participation. The conclusions highlight the necessity for transparent communication, adequate resource support, effective policy implementation, and training programmes to enhance school-parent collaboration. Recommendations include fostering regular communication, addressing resource limitations, bolstering policy implementation, and providing training and support for stakeholders.
Dissertation (M.Ed.(Education Management and Leadership))--University of the Free State, 2024
Keywords: School management teams; Parental involvement; Strategies; Collaboration; Learner academic performance